ChemInform Abstract: Michael Addition—Aromatization Reaction of Dienylimines Bearing a Leaving Group and Its Application to the Preparation of Thiol‐Selective Labeling Reagents Capable of Forming Strong Carbon—Sulfur Bonds. Issue 18 (17th April 2014) - Miyata, Okiko; et al., et al.
Abstract The fluorescence properties of the compounds (XVI), (XVII), and (XVIII) are investigated in CHCl3 and they show strong emission at about 500 nm.